Kualitas Laba dan Tingkat Manipulasi Laporan Keuangan dimata Investor Pasar Modal Sektor Pertambangan. Pentingkah? - Robith Hudaya (Valid: Jurnal Ilmiah, 2021)
This study aims to prove empirically whether the earnings quality and the level of financial statement manipulation have an effect on the company market value. The study used sample of 3 years from 2017 to 2019. Using the multiple linear regression method, it was found that the quality of earnings has a negative effect on the market value of the company and is contrary to previous theory and research. Meanwhile, the level of financial statement manipulation has no effect on the company's market value. These results indicate that the quality of earnings and the degree of manipulation of financial statements are not the main information used by capital market players in determining their investment choices. Capital market players prefer other methods of analysis in determining their investment options.